Autonomic dysfunction in clinically isolated syndrome suggestive of multiple sclerosis. Issue 1 (January 2016) - Crnošija, Luka; Adamec, Ivan; Lovrić, Mila; Junaković, Anamari; Krbot Skorić, Magdalena; Lušić, Ivo; Habek, Mario
Highlights: Composite Autonomic Scoring Scale detected sympathetic nervous system dysfunction in half of the clinically isolated syndrome (CIS) patients. The parasympathetic nervous system seems to be preserved in the early stages of multiple sclerosis. Quantitative Sudomotor Axon Reflex Test detects sudomotor dysfunction in half of the CIS patients. Abstract: Objectives: The aim of this study was to determine the extent of autonomic dysfunction in patients with clinically isolated syndrome (CIS) by using a standardized battery of autonomic tests in the form of the Composite Autonomic Scoring Scale (CASS). Methods: This was a prospective, cross sectional study which included 24 consecutive patients who were diagnosed with CIS and 17 healthy controls. In all participants, heart rate and blood pressure responses to the Valsalva maneuver, heart rate response to deep breathing and blood pressure response to passive tilt were performed. In 16 patients, Quantitative Sudomotor Axon Reflex Test (QSART) and catecholamine measurement was performed. Results: The proportion of CIS patients with pathological adrenergic index was statistically significantly higher compared to healthy controls (12 vs 2, p = 0.018), while there was no difference in cardiovagal index between groups. Five patients had a sudomotor index of 1 (in 4 there was hypohydrosis <50% and in 1 persistent foot hyperhidrosis). When combining adrenergic, cardiovagal and sudomotor index into CASS, 8 patients (50%) had evidence of autonomic dysfunction, 7 mild and one moderate. Conclusion: Sympathetic nervous system is frequently affected in CIS patients. Significance: CASS is able to detect autonomic nervous system dysfunction in CIS patients.